Efektivitas Badan Usaha Milik Desa (BUMDes) dalam meningkatkan kesejahteraan masyarakat - Ikhsan, Luthfi Ridhatul; Priatna, Wahyu Budi; Burhanuddin, Burhanuddin (Entrepreneurship Bisnis Manajemen Akuntansi (E-BISMA), 2024)
Development that starts in the village sector is the first step to run the economy of Indonesia, one of the many development programmes are the formation of the Village-Owned Enterprise (BUMDes). The presence of BUMDes is expected to be able to improve the standard of living and community welfare. Community welfare itself has a meaning that has been stated in Indonesian Law (UU No. 11 of 2009). The objectives of this study are to analyze the effectiveness of Village-Owned Enterprises that have managed their business units, to analyze the welfare of village communities affected by the operation of Village-Owned Enterprises and to analyze the influence that occurs between the effectiveness of Village-Owned Enterprises and the welfare of village communities. Descriptive analysis, paired sample T-Test, correlation and ordinal regression analysis are among those of the methode that are used in this study. The result of the study shows that there is a positive and significant correlation between the effectivity of the BUMDes and the welfare of the villagers, and there are 4 indicators of effectiveness of the BUMDes that significantly impactful to the welfare of the villagers, and it consist of sustainability, impact, empowerment, and participation.